Optimization of Solvent Extraction of Oil from Sandbox Kernels (Hura Crepitans L.) by a Response Surface Method. (1st January 2017) - Oniya, O. O.; Oyelade, J. O.; Ogunkunle, O.; Idowu, D. O.
ABSTRACT: The use of vegetable oil as feedstock for biodiesel production is controversial as a result of the challenges of a food-fuel crisis associated with the use of edible oils for biodiesel production and use of arable land for energy feedstock generation. This work, therefore, focused on the extraction of oil from non-edible seed such as sandbox seed using a solvent extraction method, evaluation of optimal conditions for oil extraction from sandbox, and testing the fuel properties of extracted sandbox oil. A Box-Behnken design of response surface methodology (RSM) with 17 experimental runs was used to investigate the optimum conditions for the extraction, and the selected variables were effective seed/solvent ratio (0.04, 0.06, 0.08 g/ml), extraction temperature (65, 60, 75ºC), and extraction time (3, 5, 7 h). Selected fuel properties (specific gravity, viscosity, cloud point, pour point, density, and refractive index) of the extracted oil were determined according to American Society for Testing Materials (ASTM) standards. The optimum oil yield (63.4%) was obtained at the seed/solvent ratio, extraction temperature, and extraction time of 0.05 g/ml, 68.13ºC, and 5 h, respectively The viscosity at 30ºC, specific gravity, density, cloud point, pour point, and refractive index of the extracted oil were 4.55 mm 2 /s, 0.91, 910 kg/m 3, 5.9 ºC, –1.0ºC, and 1.4683, respectively. Thus the result from this research work has established the optimal conditions for solvent extraction of oil from sandbox seed. The fuel properties of the sandbox oil show that it is potentially suitable to produce biodiesel that can be used to power internal combustion engines.